Decrease of gene expression of astrocytic 5-HT2B receptors parallels development of depressive phenotype in a mouse model of Parkinson’s disease - Zhang, Xique; Song, Dan; Gu, Li; Ren, Yan; Verkhratsky, Alexei; Peng, Liang (Frontiers in Cellular Neuroscience, 2015)
Astrocytes contribute to pathogenesis of neuropsychiatric disorders, including major depression. Stimulation of astroglial 5-HT2B receptors transactivates epidermal growth factor receptors (EGFRs) and regulates gene expression. Previously we reported that expression of 5-HT2B receptors in cortical astrocytes is down-regulated in animals, which developed anhedonia in response to chronic stress; moreover this down-regulation as well as anhedonia, are reversed by chronic treatment with fluoxetine. In this study we have investigated whether astrocytic 5-HT2B receptor is involved in anhedonia in C57BL/6 mice model of Parkinson’ disease (PD) induced by intraperitoneal injection of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) for 7 days. The MPTP treatment induced anhendonia in 66.7% of animals. The appearance of depressive behavior was accompanied with motor deficiency and decrease of tyrosine hydroxylase (TH) expression. Expression of mRNA and protein of 5-HT2B receptor in animals that became anhedonic decreased to 77.3 and 79.3% of control groups, respectively; in animals that received MPTP but did not develop anhedonia the expression of 5-HT2B receptor did not change. Experiments with FACS-sorted isolated cells demonstrated that decrease in 5-HT2B receptor expression was confined to astrocytes, and did not occur in neurons. Fluoxetine corrected MPTP-induced decrease of 5-HT2B receptor expression and depressive behavior. Our findings indicate that regulation of gene expression of 5-HT2B receptors in astroglia may be associated with pathophysiological evolution of PD-induced depression.